Prolonged Medical Cannabis Treatment is Associated With Quality of Life Improvement and Reduction of Analgesic Medication Consumption in Chronic Pain Patients - Aviram, Joshua; Lewitus, Gil M.; Vysotski, Yelena; Yellin, Ben; Berman, Paula; Shapira, Anna; Meiri, David (Frontiers in Pharmacology, 2021)
Introduction: Chronic non-cancer pain (CNCP) is one of the most prevalent indications for medical cannabis (MC) treatment globally. In this study, we investigated CNCP parameters in patients during prolonged MC treatment, and assessed the interrelation between CNCP parameters and the chemical composition of MC chemovar used. Methods: A cross-sectional questionnaire-based study was performed in one-month intervals for the duration of six months. Subjects were adult patients licensed for MC treatment who also reported a diagnosis of CNCP by a physician. Data included self-reported questionnaires. MC treatment features included administration route, cultivator, cultivar name and monthly dose. Comparison statistics were used to evaluate differences between the abovementioned parameters and the monthly MC chemovar doses at each time point. Results: 429, 150, 98, 71, 77 and 82 patients reported fully on their MC treatment regimens at six one-month intervals, respectively. Although pain intensities did not change during the study period, analgesic medication consumption rates decreased from 46% to 28% (p<0.005) and good Quality of Life (QoL) rates increased from 49% to 62% (p<0.05). These changes overlapped with increase in rates of (-)-Δ9-trans-tetrahydrocannabinol (THC) and α-pinene high dose consumption. Conclusions: Even though we observed that pain intensities did not improve during the study, QoL did improve and the rate of analgesic medication consumption decreased alongside with increasing rates of high dose THC and α-pinene consumption. Understanding MC treatment composition may shed light on its long-term effects.